1993
DOI: 10.1159/000261606
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Counts of Mutans Streptococci and Lactobacilli and Past Caries Experience in Caries Prediction

Abstract: Clinical and salivary factors were compared with each other for the ability to predict 3-year caries increment in a group of 122 teenagers. The group was screened according to two levels of salivary mutans streptococci and lactobacilli and comparable levels of baseline caries experience (DFS). The risk for caries was validated at three different levels. Sensitivity, specificity, and the positive and negative prediction values were calculated for each level. The results showed that the baseline caries experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
1
2

Year Published

1995
1995
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 11 publications
1
25
1
2
Order By: Relevance
“…The caries-predictive power of the mutans test among juvenile populations from Western countries with low caries incidence is under discussion [Alaluusua, 1993;Dodds and Suddick, 1995]. Even though the test is a strong caries predictor [Powell, 1998], studies on children with a low baseline caries experience have given sensitivity values lower than 50% [see, for example, Schröder et al, 1994;Grindefjord et al, 1995].…”
Section: Multiple Salivary Ms Testmentioning
confidence: 99%
“…The caries-predictive power of the mutans test among juvenile populations from Western countries with low caries incidence is under discussion [Alaluusua, 1993;Dodds and Suddick, 1995]. Even though the test is a strong caries predictor [Powell, 1998], studies on children with a low baseline caries experience have given sensitivity values lower than 50% [see, for example, Schröder et al, 1994;Grindefjord et al, 1995].…”
Section: Multiple Salivary Ms Testmentioning
confidence: 99%
“…Studies on caries risk assessment have shown that past caries experience variables compared to other variables had a relatively strong association with caries increment and that caries experience was the best predictor of caries increment in children with a mixed dentition [Klock and Krasse, 1979;Honkala et al, 1984;Wilson and Ashley, 1989;Alaluusua et al, 1990;Russell et al, 1991;Disney et al, 1992;Alaluusua, 1993;Mattiasson-Robertson and Twetman, 1993;Raitio et al, 1996]. A recent study, which used the area under the ROC curve as a method to compare the prognostic accuracy of various predictors, has reported no appreciable effect when additional predictors such as mutans streptococci and lactobacilli counts, salivary flow rate, sucrose intake frequency, brushing frequency and social group were applied in combination with past caries experience [Hausen, 1997].…”
mentioning
confidence: 99%
“…The detection of caries lesions allows an evaluation of the presence of disease activity and also of its past history, which has been quoted as the most important factor in caries risk prediction. 16,17 The present survey indirectly evaluated the ability of 151 dentists who work in three cities of southern Brazil to identify non-cavitated lesions properly. Among the professionals with more work experience -those who graduated between 1960 and 1975 -only 11 (23.9%) answered that they usually remove dental plaque before performing diagnosis.…”
Section: Discussionmentioning
confidence: 99%